Film solar cell window layer material and window layer film
Preparation of ZnO materials by sol-gel method and adding trace Mg doping, the lattice distortion and defect problems of zinc oxide window layer preparation in the traditional vacuum magnetron sputtering method is solved, the performance and efficiency of CZTSSe solar cells are improved, and the production is reduced cost.
Patent Information
- Application Number
- CN202411147508.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-13
AI Technical Summary
The traditional vacuum magnetron sputtering method prepares zinc oxide (i-ZnO) window layer with high kinetic energy particles bombardment causes lattice distortion and defects, increasing carrier recombination, and the process is complex and expensive, affecting the performance of solar cells.
ZnO material was prepared by sol-gel method as the window layer of CZTSSe solar cells. The organic weak acid salt or hydrate solution of Zn2+ was heat treated, and trace Mg doping was added to reduce oxygen vacancies defects, and the film thickness and transmission were controlled through spin coating technology. Rate.
On the premise of ensuring performance, the cost of vacuum equipment is reduced, the open circuit voltage, short circuit current density and photoelectric conversion efficiency of solar cells are improved, the carrier recombination is reduced, and the light transmittance and better electrical performance are achieved. .
Smart Images

Figure CN119133278A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solar cell materials, and in particular to a thin-film solar cell window layer material and a window layer film. Background Art
[0002] As an emerging photovoltaic technology, copper zinc tin sulfur selenium (Cu2ZnSn(S,Se)4, CZTSSe) solar cells have attracted widespread attention at home and abroad in recent years due to their environmentally friendly composition and adjustable band gap (1.0-1.5eV). The classic multilayer structure of CZTSSe solar cells is: Mo / CZTSSe / CdS / i-ZnO / ITO / Ag. According to previous studies, the interface between different functional layers affects the performance of the battery device to a certain extent. This is because in addition to exhibiting its own unique physical and chemical properties, each functional layer also has different microstructures, thermal expansion coefficients, and work functions, which easily lead to interface defects and voids.
[0003] Among them, intrinsic zinc oxide (i-ZnO) is an important component of the window layer and front interface (pn junction) of CZTSSe solar cells. In addition to being responsible for the collection and transmission of electrons, it also combines with the CdS buffer layer to form the n-type region of the pn junction, reducing the leakage of the battery device. However, i-ZnO is usually prepared by vacuum magnetron sputtering technology, which is complex and expensive to prepare. On the one hand, this will cause the heterojunction region to be bombarded by high-kinetic particles, destroying the lattice order and causing lattice distortion, and aggravating the carrier recombination in the space charge region; on the other hand, since i-ZnO is deposited by magnetron sputtering in an argon atmosphere, this oxygen-poor atmosphere will lead to more defects, such as oxygen vacancies (VO) and zinc vacancies (Zni), thereby delaying the transmission and collection of electrons. Summary of the invention
[0004] To solve the above problems, the present invention provides a method for preparing ZnO (hereinafter referred to as ZnO-SG in the present invention) by a sol-gel method to replace the traditional vacuum sputtering method to prepare i-ZnO (hereinafter referred to as ZnO-SP in the present invention) as the window layer of CZTSSe solar cells. Specifically, the technical solution of the present invention is as follows:
[0005] The first aspect of the present invention provides a thin-film solar cell window layer material, wherein the window layer material is a ZnO material prepared by a sol-gel method, wherein the ZnO material prepared by the sol-gel method is composed of Zn 2+ Organic weak acid salt or Zn 2+ A solution of a hydrate of an organic weak salt is obtained by heat treatment, wherein the organic weak salt is especially a carboxylate, and its window layer material has a band gap of not less than 3.3 eV.
[0006] In the present invention, Zn2+ Organic weak acid salt or Zn 2+ The solution of the hydrate of the organic weak acid salt is subjected to heat treatment, wherein the solution is a solution based on an organic solvent, preferably, the solvent is an ether, an alcohol, a ketone, more preferably, the solvent is a monoether, a polyether. In the implementation mode of the present invention, the solvent is based on ethylene glycol monomethyl ether.
[0007] In the present invention, the Zn 2+ The mixed solution of organic weak acid salt is Zn 2+ of acetate.
[0008] In a preferred embodiment of the present invention, the ZnO material prepared by the sol-gel method is a ZnO material doped with Mg, wherein the molar ratio of Mg to Zn in the material is 0.1-5% based on the molar amount of Zn.
[0009] In the present invention, the Mg-doped ZnO material is composed of 2+ and Mg 2+ The mixed solution of organic weak acid salt is prepared by heat treatment. 2+ and Mg 2+ A mixed solution of an organic weak acid salt, preferably Zn 2+ and Mg 2+ The carboxylate, especially acetate, is in a mixed solution, wherein the solvent of the solution includes ether, alcohol, ketone, etc., especially monoether, polyether, etc.
[0010] In a preferred embodiment of the present invention, based on Zn 2+ Molar amount, Mg 2+ With Zn 2+ The molar ratio of Mg to Zn in the material is 1%, which corresponds to the Mg-doped ZnO material finally prepared. Wherein, based on the molar amount of Zn, the molar ratio of Mg to Zn in the material is 1%.
[0011] The second aspect of the present invention is to provide a thin-film solar cell window layer film prepared from a thin-film solar cell window layer material and an application of the material in the preparation of a thin-film solar cell.
[0012] The thickness of the window layer film is 40-80nm, preferably 40-60nm, and especially 50nm. It has a light transmittance of not less than 90% in the wavelength band of 400-800nm, preferably, a light transmittance of not less than 93%, and more preferably, a light transmittance of not less than 94%. It has a light transmittance of not less than 90% in the wavelength band of 400-600nm, preferably, a light transmittance of not less than 93%, and more preferably, a light transmittance of not less than 94%.
[0013] The present invention adopts a sol-gel method to prepare ZnO-SG material and ZnO-SG with different Mg doping contents, and prepares a thin film based on the material as a window layer to replace the traditional ZnO-SP, which can greatly reduce the cost of vacuum equipment and its preparation while ensuring performance. The present invention finds that the incorporation of trace Mg reduces the oxygen vacancy defects in the ZnO-SG window layer; the CZTSSe solar cells with ZnO-SG window layers with different Mg doping contents are characterized and analyzed. When the Mg doping content in the ZnO-SG window layer is 1%, the battery device has different degrees of improvement in Voc, Jsc and FF. In addition, trace Mg doped into the ZnO-SG window layer effectively reduces the carrier recombination at the front interface of the battery, and finally obtains a photoelectric conversion efficiency of 9.33%. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 : (a) Schematic diagram of undoped and doped ZnO precursor sols with different Mg contents;
[0015] Figure 2 : XRD patterns of ZnO-SP and ZnO-SG films;
[0016] Figure 3 :(a) transmittance spectra and (b) relationship curves of (αhν)2 and hν of ZnO-SP and ZnO-SG films;
[0017] Figure 4 : JV performance test curve of ZnO-SP and ZnO-SG as window layers after assembling into devices;
[0018] Figure 5 : (a) XRD patterns and (b) (110) diffraction patterns of ZnO-SG films with different Mg doping contents;
[0019] Figure 6 :Surface EDS Mapping of ZnO-SG-Mg1;
[0020] Figure 7 : XPS spectra of ZnO-SG and ZnO-SG-Mg1 thin film samples;
[0021] Figure 8 : Photoluminescence spectra of ZnO-SG films with different Mg doping contents;
[0022] Fig. 9 : JV curves of CZTSSe solar cell devices assembled with ZnO-SG films with different Mg doping contents. DETAILED DESCRIPTION
[0023] 1. Pretreatment and preparation of ZnO sol
[0024] The ZnO semiconductor thin film material prepared by the sol-gel method in this embodiment is obtained by dissolving Zn(CH3COOH)2·2H2O in 2-methoxyethano l(MOE), and the concentration of the prepared solution is 0.45 M. When optimizing the ZnO film, Mg(CH3COOH)2·4H2O is used as the Mg source, and sols with atomic molar percentages of Zn / Mg of 0%, 1%, 2%, 3% and 5% are prepared.
[0025] Specifically, first, use a diluted solution of deionized water: detergent at a ratio of 10:1 to ultrasonically clean the screw-mouth bottle for 30 minutes, then use deionized water to clean it, and then use high-pressure pure water to rinse the inside and outside of the screw-mouth bottle and its accessories. Use a high-pressure, high-purity nitrogen gun to blow dry the cleaned screw-mouth bottle and its accessories to prevent contamination.
[0026] Weigh Zn(CH3COOH)2·2H2O on a high-precision analytical balance and put it into a cleaned screw-mouth bottle. Then use a pipette to extract 5 ml of MOE and squeeze it into the above screw-mouth bottle to prepare a sol with a concentration of 0.45 M. Seal the mouth of the screw-mouth bottle with a sealing gel, put it into a sealed bag, and put it into an ultrasonic instrument for ultrasonic dispersion treatment for 30 minutes.
[0027] The sol obtained in the above steps was stirred at room temperature for 30 min using a magnetic rotor at a speed of 500, during which the bottle cap was checked for drug residue.
[0028] Ethanolamine solution was added dropwise to the sol as a stabilizer, and the molar ratio of ethanolamine to metal cation was 1: 1. After stirring at room temperature for 20 minutes, ultrasonic dispersion treatment was performed for 20 minutes, and then stirring was continued at 60°C for 2 hours, and finally stirred at room temperature for 12 hours to obtain a transparent and uniform sol.
[0029] The bottle mouth was sealed with sealing gel and placed in a room temperature environment for natural aging for 24 hours. The sol obtained by aging was filtered through a polytetrafluoroethylene filter and placed in a cleaned screw-mouth bottle for later use.
[0030] 2. Preparation of ZnO-SG thin films on glass substrates
[0031] Use a 1.1mm thick soda-lime glass (SLG) substrate and cut it into 2*2cm size using a glass cutter. Put the cut soda-lime glass piece into a beaker, prepare and add a 20:1 deionized water: detergent mixed solution, and place it in a 65° water bath for 2 hours; then scrub the soda-lime glass piece and rinse it with deionized water, place the soda-lime glass piece on a polytetrafluoroethylene rack and put it into a beaker with 300ml deionized water, and perform ultrasonic cleaning 3 times*30min. Replace the newly prepared deionized water each time; then put the soda-lime glass piece into a beaker containing a 1:1:1 solution of isopropanol:acetone:methanol, and repeat the ultrasonic cleaning 3 times, each time for 30min; then rinse the glass piece with deionized water, and then put it into a beaker containing deionized water for ultrasonic cleaning 3 times*30min. Freshly prepared deionized water was replaced each time; the soda-lime glass piece was then placed in a beaker containing anhydrous ethanol and ultrasonically cleaned for 30 minutes; the soda-lime glass piece was then placed in an oven to dry and store.
[0032] The soda-lime glass substrate was treated with an ultraviolet ozone cleaning device for 15 minutes to remove organic matter and unpaired chemical bonds on the substrate surface to increase the wettability of the sol on the substrate.
[0033] The filtered sol was evenly drop-coated on the treated soda-lime glass substrate and spin-coated at 3000 rpm for 30 seconds. The spin-coated film sample was then heat-treated on a constant temperature heating table at 150°C under air for 30 minutes. After repeating the spin coating twice, the film was evenly deposited on the soda-lime glass substrate and reached a thickness similar to that of i-ZnO (the thickness of i-ZnO was 51.8 nm as tested by a surface profiler).
[0034] Through surface profiler test, SEM test, XRD test, UV-visible spectrophotometer test, it was determined that the thickness of ZnO-SG semiconductor film is comparable to that of ZnO-SP film, the phase structure is consistent, and the average transmittance is 88% (the average transmittance of ZnO-SP film is 79%). Higher transmittance is conducive to the CZTSSe absorption layer to absorb more incident light. The fitted ZnO-SG film band gap (3.40eV) is also higher than the band gap of ZnO-SP (3.22eV). Subsequently, ZnO-SG and ZnO-SG semiconductor films were assembled into CZTSSe thin film solar cells as window layers and tested and analyzed.
[0035] 3. Preparation of solar cells containing ZnO-SG window layer
[0036] A Mo layer about 800nm thick was sputtered on a dried and cleaned soda-lime glass substrate by DC magnetron sputtering as the back electrode of the CZTSSe solar cell. Specifically, it includes a two-step deposition process of the bottom layer and the top layer. The thickness of the two layers of Mo is about 400nm. When the bottom layer of Mo is prepared, a higher power is used, which can be well deposited and adhered to the soda-lime glass substrate, thereby effectively preventing it from falling off during the preparation of other functional layers; when the top layer of Mo is prepared, a lower power is used, so that it has excellent conductivity, which helps to reduce the resistance of the back electrode and improve the transmission and collection capacity of hole carriers. The specific sputtering process parameters of the two layers of Mo are shown in Table 1.
[0037] Table 1. Mo sputtering process parameters
[0038]
[0039] Take out the screw-mouth glass bottle and rotor from the aqua regia bucket respectively and clean them ultrasonically with deionized water and anhydrous ethanol in turn, ensuring that they are thoroughly cleaned and then dried for later use.
[0040] Weigh 1.1408g of Cu(CH3COOH)2·H2O and 0.8864g of SnCl2·2H2O powder and add them to the dried screw-mouth glass bottle in turn. Then inject 5ml of DMSO solvent into the bottle via a syringe. Seal the screw-mouth bottle with sealing glue and place it on a magnetic stirrer. Stir for 12 hours at room temperature to obtain a light green solution. Weigh 0.5603g of ZnCl2 and add it to the screw-mouth bottle where stirring has stopped. Seal it and continue stirring for about 1 hour until it is completely dissolved. Finally, add 1.6g of SC(NH2)2 to the bottle, seal it with sealing glue and continue stirring for 2 hours. The solution first turns black with slight heat, and finally turns light yellow as SC(NH2)2 dissolves. At this point, the copper zinc tin sulfur (CZTS) precursor solution is prepared, and the above process is all carried out in air.
[0041] The molybdenum (Mo)-plated substrate on the soda-lime glass was treated with an ultraviolet ozone cleaning device for 15 minutes to remove organic matter and unpaired chemical bonds on the surface of the substrate to improve the wettability of the sol and the CZTS precursor solution on the substrate.
[0042] In a glove box filled with N2 (water and oxygen are less than 10ppm), the CZTS precursor solution prepared above is filtered with a polytetrafluoroethylene filter, and then the CZTS precursor solution is evenly spin-coated on the Mo-plated substrate. The spin coater rotates at 3000rpm for 30s to evenly coat the surface of the substrate with the precursor solution. The spin-coated CZTS precursor film is placed on a heating table (the temperature is set to 430℃) for baking. After 3 minutes, the sample is removed and the spin coating is continued after it is naturally cooled. Repeat the above process 5 times to obtain a CZTS precursor film.
[0043] The prepared precursor film was placed in a graphite box containing Se particles, the N2 flow rate was adjusted to 80 sccm, the selenization program was set to rise from room temperature to 540°C in 1 minute, and kept warm for 20 minutes, and clicked Start to start the selenization process. After the selenization was completed, the furnace was allowed to cool naturally to room temperature to obtain the CZTSSe absorption layer film.
[0044] Cadmium sulfide (CdS) acts as a buffer layer in solar cells. A CdS film of about 50 nm was deposited on the surface of the CZTSSe absorption layer using a chemical bath method (CBD). The specific preparation process includes: placing a beaker containing 250 ml of deionized water on a stirring table at 500 rpm for continuous stirring. Then weigh 0.0768 g of cadmium sulfate powder with an electronic balance, add it to the beaker and stir for 5 minutes until the powder is completely dissolved. Then use a dropper to drip 12.5 ml of ammonia water and continue stirring for 5 minutes. After that, the polytetrafluoroethylene sample rack containing the CZTSSe sample is hung on the beaker, and the solution in the beaker completely covers the CZTSSe sample. Then add 0.11 g of thiourea to the solution and continue stirring for 5 minutes. After the stirring process is completed, the beaker is transferred to a water bath (the temperature is set to 70°C) for heating and stirring until the color of the film surface changes from grayish white to blue-purple. The film surface was rinsed with deionized water and anhydrous ethanol in turn and then placed in a drying oven at 60°C for drying.
[0045] Subsequently, a portion of the prepared CdS thin film samples was placed on a special mask plate, and then placed in a magnetron sputtering chamber, and vacuuming, pre-sputtering and sputtering were performed in sequence to prepare ZnO-SP (thickness 50nm); the other portion of the samples was prepared to prepare ZnO-SG. The above samples were then deposited with a 200nm low-resistance indium tin oxide window layer film using the radio frequency magnetron sputtering method. The process parameters used in the sputtering method are shown in Table 2.
[0046] Table 2. Sputtering process parameters of i-ZnO and I TO window layers
[0047]
[0048] Ag was deposited on the surface of the sputtered window layer by thermal evaporation as the top electrode with a thickness of 100 nm. Finally, the sample was mechanically scribed into 9 lines with an effective area of 0.19 cm 2 An independent cell device was prepared. Thus, CZTSSe thin film solar cells with high resistance window layers of ZnO-SG and ZnO-SP thin films were prepared and their performance was tested.
[0049] The JV test of the battery shows that the open circuit voltage (Voc) and short circuit current density (Jsc) of the device using the ZnO-SG window layer are improved to varying degrees compared with those of the ZnO-SP. Voc increases from 428.32mV to 433.32mV, which is due to the better ohmic contact of ZnO-SG. Jsc increases from 31.38mA / cm 2 Increased to 32.56mA / cm 2 , which is due to the higher light transmittance and better optical performance of its window layer. However, the filling factor (FF) of ZnO-SG is 57.02%, which is slightly lower than that of ZnO-SP at 58.18%. The energy level position of ZnO-SG film and oxygen vacancy defects are the main reasons for the reduction of FF in ZnO-SG devices. The diode ideality factor A value and reverse saturation current density J0 of ZnO-SG are larger than those of ZnO-SP, indicating that the carrier recombination at the interface of ZnO-SG is aggravated, which is not conducive to carrier transport and collection. In view of the above problems of ZnO-SG, by doping an appropriate amount of Mg element in its window layer, adjusting the energy level position of the window layer to reduce the band offset between the CdS buffer layer and reduce oxygen vacancies, the carrier recombination at the front interface is suppressed.
[0050] In an embodiment of the present invention, the ZnO film is further optimized according to the above scheme. In the pretreatment and preparation steps of the ZnO sol, sols with atomic molar percentages of Zn / Mg of 0%, 1%, 2%, 3% and 5% are prepared. Except for the additional addition of Mg source, the preparation process is consistent with the description above.
[0051] The present invention tests the ZnO-SG semiconductor film doped with different contents of Mg. When the Mg doping amount is 1%, the ZnO-SG film exhibits the best optical and electrical properties. It is further assembled into a CZTSSe solar cell, and the assembly process is consistent with the above. After assembly, performance tests are performed. The relevant test results are as follows:
[0052] See also Figure 1 , where (a) is the ZnO precursor sol without and with different Mg content, and (b) is the SEM cross-sectional view of the thickness of the ZnO film spun on a cleaned soda-lime glass substrate. The thickness of the ZnO window layer obtained by spin coating using the sol-gel method in the present invention is similar to the thickness of the window layer prepared by the vacuum magnetron sputtering method, indicating that the sol-gel method can control the required thickness of the film.
[0053] Figure 2The XRD patterns of ZnO-SP and ZnO-SG films are shown in Figure 2. The physical structures of ZnO-SP and ZnO-SG films were analyzed by XRD. The results show that ZnO-SP has two obvious characteristic diffraction peaks, which are (002) and (103) crystal planes. ZnO-SG has five characteristic diffraction peaks, which are (100), (002), (101), (110) and (112) crystal planes. The XRD results show that both groups of film samples have the typical wurtzite structure of ZnO, but the diffraction peak intensity of ZnO-SG is lower than that of ZnO-SP, which means that the crystallinity of ZnO-SG is relatively low. However, the lower crystallinity of ZnO-SG is beneficial to provide a flat surface for the subsequent deposition of I TO on the one hand, and to reduce its own stress on the other hand.
[0054] Figure 3 (a) Transmittance spectrum of ZnO-SP and ZnO-SG films and (b) the relationship curve between (αhν)2 and hν; As the window layer of CZTSSe solar cells, ZnO usually needs to have excellent light transmittance. As shown in the figure, the transmittance of the two groups of film samples was tested and analyzed by UV-visible spectrophotometer. It can be clearly seen that the transmittance of ZnO-SP in the wavelength range of 350-800nm is relatively low, with an average transmittance of 79%. The transmittance of ZnO-SG is significantly higher than that of ZnO-SP, with an average transmittance of 88%. Higher transmittance is conducive to the CZTSSe absorption layer to absorb more incident light. Figure 3 (b) is the optical band gap calculated based on the transmission spectra of the two sets of films. It can be found that the band gap of ZnO-SG (3.40 eV) is higher than that of ZnO-SP (3.22 eV).
[0055] in Figure 3 (a) The light transmittance of the main wavelength nodes of each sample is shown in the following table
[0056]
[0057] Figure 4 This is the JV performance test curve of the device assembled with ZnO-SP and ZnO-SG as window layers.
[0058] Figure 5 (a) XRD patterns and (b) magnified images of the (110) diffraction peak of ZnO-SG films with different Mg doping contents; ZnO-SG films with Mg doping contents of 0%, 1%, 2%, 3% and 5% were prepared by direct spin coating on a cleaned soda-lime glass substrate, and XRD tests were performed to explore the effect of different Mg doping contents on the phase structure of ZnO-SG films. Figure 5(a) is the XRD spectrum of five groups of thin film samples. It can be found that the characteristic diffraction peaks of all samples come from the hexagonal wurtzite structure of ZnO, and no impurities are detected, indicating that trace Mg ion doping does not affect the crystal structure of ZnO-SG. Figure 5 (b) It can be observed that as the Mg content increases, the (110) diffraction peak gradually moves to a higher angle. This is because when the Mg (0.570) element with a smaller ionic radius replaces the Zn (0.600) element with a larger ionic radius, the lattice shrinks, causing the crystal plane of ZnO-SG to shift to a high angle. The movement of the XRD diffraction peak further confirms that Mg ions are successfully incorporated into the ZnO-SG lattice.
[0059] Figure 6 This is the surface EDS Mapping diagram of ZnO-SG-Mg1; it can be seen that the Zn, Mg, and O elements in the film are distributed relatively evenly without aggregation, indicating that ZnO-SG-Mg1 is uniformly deposited on SLG.
[0060] Figure 7 XPS spectra of ZnO-SG and ZnO-SG-Mg1 thin film samples; XPS tests were performed on ZnO-SG and ZnO-SG-Mg1 to explore the evolution of the valence states of each element, and the test results are shown in the figure. Figure 7 (a) For the Zn2p peak, Zn2p was observed in both groups of film samples. 1 / 2 (1044.4eV) and Zn2p 3 / 2 (1021.3 eV), the peak position did not shift and the corresponding binding energy remained consistent, indicating that the incorporation of Mg did not change the chemical environment of Zn. Figure 7 In (b), the Mg1 s peak fluctuation was observed at around 1303.5 eV in ZnO-SG-Mg1, indicating that Mg was successfully incorporated into the ZnO-SG main lattice, which is consistent with the XRD test results. Figure 7 The O1 s spectrum in (c) can be fitted into two single peaks, which are centered at 529.9±0.1eV (OM) and 531.7±0.1eV (OV), respectively. OM represents oxygen in the lattice, which is fully bonded to the surrounding atoms, and OV is attributed to oxygen vacancies. According to calculations, the relative content of oxygen vacancies in ZnO-SG-Mg1 (62.8%) is lower than that in ZnO-SG (66.2%), which means that the addition of 1% Mg suppresses the defect state of ZnO-SG and reduces oxygen vacancies. This is because trace amounts of Mg and Zn undergo equivalent substitution. Although there is no change in the charge, the ionicity of Mg is stronger than that of Zn, that is, the Mg-O bond has stronger ionic characteristics than the Zn-O bond. Therefore, the addition of trace amounts of Mg can more effectively bind oxygen, thereby reducing the concentration of oxygen vacancies.
[0061] Figure 8 The photoluminescence spectra of ZnO-SG films with different Mg doping contents are shown in Figure 2. They all have two luminescence peaks, namely, the ultraviolet luminescence peak (bandgap emission peak) at about 376nm and the green luminescence peak at about 510nm. The ultraviolet luminescence peak is related to the free exciton recombination of ZnO itself. It can be seen from the figure that the five groups of films all have narrow and strong ultraviolet luminescence peaks near 376nm, and as the Mg doping content increases, the ultraviolet luminescence peaks produce a blue shift phenomenon. This is mainly due to the increase in the optical band gap after Mg is doped into ZnO-SG. The generation of the green luminescence peak in the visible light region mainly comes from oxygen vacancies (VO). It can be found from the figure that the intensity of the green luminescence peak shows a trend of first decreasing and then increasing with the increase of Mg doping content. Among them, the green luminescence peak intensity of ZnO-SG-Mg1 is the lowest and the oxygen vacancy content is the least, indicating that the oxygen vacancy concentration of ZnO-SG is reduced after 1% Mg is doped, which is consistent with the XPS test results.
[0062] Fig. 9 JV curves of CZTSSe solar cell devices assembled with ZnO-SG thin films with different Mg doping contents; the device assembled with the optimal ZnO-SG-Mg1 thin film obtains the best photovoltaic performance.
[0063] The present invention introduces Mg element as a doping element into the ZnO-SG window layer, and systematically explores the effects of 1%, 2%, 3%, 4% and 5% Mg doping content of the ZnO-SG window layer on the battery. Since the radius of Mg2+ ions is similar to that of Zn2+ ions, the addition of trace Mg does not cause obvious distortion of the ZnO-SG lattice. At the same time, the present invention adopts a sol-gel method to prepare ZnO-SG films with different Mg doping contents as window layers instead of traditional ZnO-SP, which can greatly reduce the cost of vacuum equipment and its preparation while ensuring performance.
[0064] The experimental results show that the incorporation of trace Mg reduces the oxygen vacancy defects in the ZnO-SG window layer; CZTSSe solar cells with ZnO-SG window layers with different Mg doping contents are characterized and analyzed. The results show that when the Mg doping content in the ZnO-SG window layer is 1%, the Voc, Jsc and FF of the battery device are improved to varying degrees. In addition, trace Mg doping in the ZnO-SG window layer effectively reduces the carrier recombination at the front interface of the battery, and the photoelectric conversion efficiency of the CZTSSe solar cell is increased by 16% (the photoelectric conversion efficiency of the solar cell is increased from 8.05% to 9.33%).
Claims
1. A thin-film solar cell window layer material, characterized in that: The window layer material is a ZnO material prepared by a sol-gel method. 2+ The window layer material is obtained by heat treating a solution prepared from an organic weak acid salt or a hydrate of its salt, and has a band gap of not less than 3.3 eV.
2. The thin-film solar cell window layer material according to claim 1, characterized in that: The window layer material has a band gap of not less than 3.4 eV.
3. The thin-film solar cell window layer material according to claim 1, characterized in that: The Zn 2+ The mixed solution of organic weak acid salt is Zn 2+ of carboxylates.
4. The thin-film solar cell window layer material according to claim 1, characterized in that: The ZnO material prepared by the sol-gel method further includes a Mg-doped ZnO material prepared by the sol-gel method.
5. The thin-film solar cell window layer material according to claim 4, characterized in that: In the material, based on the molar amount of Zn, the molar ratio of Mg to Zn is 0.1-5%, preferably, the molar ratio of Mg to Zn is 1%.
6. The thin-film solar cell window layer material according to claim 4, characterized in that: The Mg-doped ZnO material comprises Zn 2+ and Mg 2+ The mixed solution of organic weak acid salt is prepared by heat treatment.
7. The thin-film solar cell window layer material according to claim 6, characterized in that: The Zn 2+ and Mg 2+ The mixed solution of organic weak acid salt is Zn 2+ and Mg 2+ The mixed solution of acetate, the heat treatment temperature is 150°C.
8. The thin-film solar cell window layer material according to claim 6, characterized in that: Based on Zn 2+ Molar amount, Mg 2+ Zn 2+ The molar ratio is 1%.
9. The thin-film solar cell window layer material according to claim 1, characterized in that: The solution is an organic solvent-based solution, preferably, the solvent is ether, alcohol, ketone, more preferably, the solvent is monoether, polyether.
10. A window layer thin film prepared according to the window layer material according to any one of claims 1 to 9, characterized in that: The thickness is 40 to 80 nm, and the light transmittance is not less than 90% in the wavelength band of 400 to 800 nm.
